Between informality and insecurity: New food and commercial dynamics in the San Roque market in Quito - Rojas-Galindo , Mariuxi Paola (2024)
As a result of COVID-19, new dynamics emerged in many urban systems, including the acquisition and distribution of food. The pandemic revealed vulnerabilities in the functioning of facilities and intensified problems such as informality, insecurity, and immigration. In order to contribute to the identification and characterization of these dynamics within food markets, a case study methodology was adopted for this article using mixed techniques – a quantitative approach using a survey and a qualitative approach featuring a focus group. Both methods were applied in the San Roque market in the Metropolitan District of Quito, an iconic food market and distribution facility. The results highlight new commercial dynamics and preferences, as in recent years informal trade and the presence of supermarket chains have proliferated; new logistic means have been created; and wholesale trade has intensified. In addition, the pandemic accentuated the vulnerability of the market at the administrative level and the precariousness of some informal jobs, in turn, accelerated changes among traders. It is concluded that these dynamics merit new conceptual, organizational, and spatial approaches in architectural and urban terms, as well as different policies that favor the sustainable management of markets.